Kultūrizglītības pilnveides iespējas Krimuldas novadā Eiropas un Latvijas kultūras attīstības tendenču kontekstā. - Olekša, Irēna (Latvijas Universitāte, 2012)
Maģistra darba “Kultūrizglītības pilnveides iespējas Krimuldas novadā Latvijas un Eiropas kultūrizglītības attīstības tendenču kontekstā” mērķis ir kultūrizglītības pilnveides iespēju apzināšana Krimuldas novadā, balstoties uz kultūrizglītības sistēmas un attīstības tendenču analīzi un priekšlikumu izstrādāšana kultūrizglītības attīstībai novadā. Tēmas aktualitāte pamatota ar Latvijā ritošo kultūrizglītības reformu un akcentu maiņu kultūrizglītības attīstībā. Aktuālās tendences kultūrizglītības attīstībā ir radošuma nozīmes apzināšana un tā loma ceļā uz zināšanu sabiedrību. Maģistra darba pētījuma jautājums ir: kādi ir iespējamie risinājumi kultūrizglītības pilnveidei Krimuldas novadā? Lai atbildētu uz šo jautājumu, darba teorētiskajā daļā ir veikta uzziņu avotu, literatūras, kultūrizglītības dokumentu analīze par kultūrizglītību un tās attīstības tendencēm. Darba empīriski pētnieciskajā daļā apzināta situācija kultūrvidē Krimuldas novadā un izstrādāti priekšlikumi kultūrizglītības attīstībai. Pētījuma rezultāti apliecina, ka kultūrizglītībai ir būtiska loma novada attīstībā un ir iespējams to pilnveidot, izmantojot autores izstrādātos priekšlikumus.

The objective of the master paper “Opportunities of Development of Culture Education at Krimulda’s Municipality in Context with Culture Development Tendencies in Europe and Latvia” is to study opportunities of the development of culture education at Krimulda’s municipality, based on analysis of culture education system and development tendencies, and to develop proposal for development of culture education at municipality. The topicality of the theme is based on culture education reform in Latvia and the change of emphasis in the culture education. The topical tendency in the culture education is to recognize importance of creativity and its part in the way towards a knowledge society. The research question is: what are the possible solutions to develop the culture education in Krimuldas’s municipality? To give answer on the research question the method of analysis of documents and literature on the culture education and its development tendencies is used in the theoretical part of the master paper. In the empirical part of research, situation at Krimulda’s municipality is shown and the author has given proposals for development of the culture education. The results of the research confirm that culture education has important part in the development of area and it is possible to develop culture education in municipality using suggestions of author.
Opportunities of Development of Culture Education at Krimulda's Municipality in the Context with Culture Development Tendencies in Europe and Latvia.
Keywords: Izglītības vadība